Sir Cumference and the Great Knight of Angleland : a math adventure - Neuschwander, Cindy; Geehan, Wayne (Watertown, MA : Charlesbridge, 2001)
To earn his knighthood, Radius must find and rescue a missing king. His father, Sir Cumference, and his mother, Lady Di of Ameter, give him a circular medallion, (a protractor), that he uses to find his way through a maze of many angles.
School Library Journal.
3-6.
Keywords: Geometry -- Juvenile literature; Geometry; Geometry